KONSEP DASAR KURIKULUM PENDIDIKAN DI SDII LUQMAN AL HAKIM BATAM - Ahmad Denico (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the basic concept of the educational curriculum applied at SDII Luqman Al Hakim Batam. The curriculum is an important element in the education system that determines the direction, goals, and teaching methods used to achieve student competencies. SDII Luqman Al Hakim Batam has a unique and comprehensive curriculum designed to integrate Islamic values ​​with general knowledge. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and document analysis related to the school curriculum. The results of the study indicate that the curriculum at SDII Luqman Al Hakim Batam prioritizes the formation of student character, improving critical thinking skills, and mastery of science and technology. In addition, this curriculum also pays attention to the individual needs of students and encourages active participation of parents in the education process. The implications of this study are expected to be a reference for curriculum development in other similar schools.